2017
DOI: 10.5465/ambpp.2017.11533abstract
|View full text |Cite
|
Sign up to set email alerts
|

Freemium Pricing: Evidence from a Large-scale Field Experiment

Abstract: AcknowledgementsWe wish to thank Michaela Draganska for helpful comments. We are further grateful for helpful discussions with: Art Owen, Stephan Seiler, Udo Wagner, Eric Seufert, participants of the Conference on Digital Experimentation at MIT, participants of the Media Economics Workshop at ETH Zuerich and seminar participants at the Institute of Marketing of Humboldt University Berlin and at the Institute for Strategy, Technology and Organization of Ludwig-Maximilians-University Munich. Finally, we wish to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…First, it relates to a nascent stream of empirical research on freemium pricing when firms offer both a free and a paid version of a digital product. Existing research has demonstrated the effect of providing a free version in various contexts such as software (Chen et al, 2017;Lee and Tan, 2013;Runge et al, 2016), cloud storage (Lee et al, 2017), digital TV service (Foubert and Gijsbrechts, 2016) and on-demand dramas (Hoang and Kauffman, 2018). For apps on Google Play, Liu et al (2014) find that paid apps with a free counterpart receive more sales than those that do not have a free counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…First, it relates to a nascent stream of empirical research on freemium pricing when firms offer both a free and a paid version of a digital product. Existing research has demonstrated the effect of providing a free version in various contexts such as software (Chen et al, 2017;Lee and Tan, 2013;Runge et al, 2016), cloud storage (Lee et al, 2017), digital TV service (Foubert and Gijsbrechts, 2016) and on-demand dramas (Hoang and Kauffman, 2018). For apps on Google Play, Liu et al (2014) find that paid apps with a free counterpart receive more sales than those that do not have a free counterpart.…”
Section: Introductionmentioning
confidence: 99%